Multiple Solutions Approach (MSA): Conceptions and Practices of Primary School Teachers in Ghana - Nabie, Michael Johnsn; Raheem, Kolawole; Agbemaka, John Bijou; Sabtiwu, Rufai (International Journal of Research in Education and Science, 2016)
The study explored the curriculum guidelines and primary school teachers’ conceptions and practices of the Multiple Solutions Approach (MSA) in teaching mathematics using basic qualitative research design. Informal conversation interviews (ICIs), observations, video and document analyses were used to collect data. Participants included a purposive sample of five practicing teachers from three districts of the Central Region of Ghana. Descriptive analytical procedures were applied to the quantitative data while the qualitative data were analyzed thematically. Findings indicated that the curriculum materials lacked concrete direction for MSA and less than 22% of sub-topics were presented in different ways: a provision that is insufficient to guide and stimulate teachers to teach in multiple ways. Teachers also lacked a clear understanding of the MSA. Although the curriculum policy encouraged MSA, teachers’ practices were inconsistent with the curriculum guidelines. The implementation of MSA was limited by inadequate curriculum provisions and teacher knowledge.